Biochemical and histological study of the effect of sterol extract from pistachio on the level of antioxidants in the liver tissue green - Esraa Ali Abdul kareem; Abdul Monaim Hamad Majeed; Rafah Razooq Hammed (Tikrit Journal of Pure Science, 2023)
The effect of sterol extract of pistachio on the levels of anti- oxidant was carried out in liver tissue of adult male rabbit, twenty eight of local rabbite, weigh range(800-1500)g. The animals was divided randomly into 4 groups (7 rabbits in each group). three groups G1,G2 and G3 in was treated orally with (50,100,150) mg/kg of sterol extract of pistachio respectively for a period of 30 days, after the end of the experiment starved rabbits for 12 hours and then seduced by the use of ether after anesthesia animal transfer to a bowl anatomy as proven front and rear sides of the animal Baldbabis and then worked an opening in the the abdomen to the sternum was extracted liver tissue as it was saved in the solution Alveslchi was estimated antioxidants in liver tissue, including the glutathione(GSH) and malon dialdehyde (MDA). The results showed that the glutathion level significantly increased in liver tissue in all groups compared with control, while the MDA level significantly increased in liver tissue in G2,G3 compared with control, While the results of microscopic histological study showed that the treatment groups sterol extract raw green pistachios be free from the distortions in addition to the lack of a change in the nature of the liver tissue.